Ex Vivo Major Histocompatibility Complex I Knockdown Prolongs Rejection-free Allograft Survival - Chang, Jessica B. (Plast Reconstr Surg Glob Open, 2018)
BACKGROUND: Widespread application of vascularized composite allotransplantation (VCA) is currently limited by the required lifelong systemic immunosuppression and its associated morbidity and mortality. This study evaluated the efficacy of ex vivo (after procurement but before transplantation) engineering of allografts using small interfering RNA to knockdown major histocompatibility complex I (MHC-I) and prolong rejection-free survival. METHODS: Endothelial cells (ECs) were transfected with small interfering RNA targeted against MHC-I (siMHC-I) for all in vitro experiments. MHC-I surface expression and knockdown duration were evaluated using quantitative polymerase chain reaction (qPCR) and flow cytometry. After stimulating Lewis recipient cytotoxic lymphocytes (CTL) with allogeneic controls or siMHC-I–silenced ECs, lymphocyte proliferation, CTL-mediated and natural killer–mediated EC lysis were measured. Using an established VCA rat model, allografts were perfused ex vivo with siMHC-I before transplantation. Allografts were analyzed for MHC-I expression and clinical/histologic evidence of rejection. RESULTS: Treatment with siMHC-I resulted in 80% knockdown of mRNA and 87% reduction in cell surface expression for up to 7 days in vitro (P < 0.05). Treatment of ECs with siMHC-I reduced lymphocyte proliferation and CTL-mediated cytotoxicity (77% and 50%, respectively, P < 0.01), without increasing natural killer–mediated cytotoxicity (P = 0.66). In a rat VCA model, ex vivo perfusion with siMHC-I reduced expression in all tissue compartments by at least 50% (P < 0.05). Knockdown prolonged rejection-free survival by 60% compared with nonsense-treated controls (P < 0.05). CONCLUSIONS: Ex vivo siMHC-I engineering can effectively modify allografts and significantly prolong rejection-free allograft survival. This novel approach may help reduce future systemic immunosuppression requirements in VCA recipients.